2019
DOI: 10.1002/jcc.26071
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Sized Ammonia Clusters and Solvation Energies of the Proton in Ammonia

Abstract: The absolute solvation energies (free energies and enthalpies) of the proton in ammonia are used to compute the pKa of species embedded in ammonia. They are also used to compute the solvation energies of other ions in ammonia. Despite their importance, it is not possible to determine experimentally the solvation energies of the proton in a given solvent. We propose in this work a direct approach to compute the solvation energies of the proton in ammonia from large‐sized neutral and protonated ammonia clusters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 69 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…Malloum studied a series of ammonia clusters [90, 252, 253], including (NH 3 ) 20,30,40,50 and H + (NH 3 ) 18,20,25,30,40,50 . The infrared (IR) spectra computed using these GMs agree quite well with experimental spectra.…”
Section: Applicationsmentioning
confidence: 74%
“…Malloum studied a series of ammonia clusters [90, 252, 253], including (NH 3 ) 20,30,40,50 and H + (NH 3 ) 18,20,25,30,40,50 . The infrared (IR) spectra computed using these GMs agree quite well with experimental spectra.…”
Section: Applicationsmentioning
confidence: 74%
“…Investigation of ammonia cluster cations has a long history. Two kinds of ammonia cluster cations are known from previous studies: protonated (H + (NH 3 ) n ) and unprotonated ((NH 3 ) n + ). The core reactions to form ammonia cluster cations are expressed by eqs and , …”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the free energies requires the calculation of frequencies; thus, the relative populations are reported in this work at the MN15/6‐31++G(d,p) level of theory. It is worth mentioning that TEMPO has been successfully applied in our previous works to derive the relative populations of neutral and protonated ammonia clusters, hydrated sodium clusters, neutral and protonated methanol clusters, neutral and protonated water clusters and solvated ferrousion and copper ion in ammonia 35‐37,39,70,71 . In those works, the reported relative populations were supported by infrared spectroscopic studies, where good agreements with experiments were found.…”
Section: Resultsmentioning
confidence: 62%